Homosexuality in Renaissance and Enlightenment England : literary representations in historical context - Summers, Claude (London : Harrington Park Press, 1992)
Fonds Suzan Daniel (FSD)ook uitgegeven als Journal of Homosexuality 23(1992) 1-2
Engels
Monografie